Genetic variability, heritability and correlation studies in soybean (Glycine max) - S, Nayana R; Fakrudin, B (The Indian Journal of Agricultural Sciences, 2020)
Genetic variability parameters and correlation among 11 quantitative traits were studied in 219 soybean working collection during kharif 2014-15 at Bengaluru. Analysis of variance revealed significant differences among the 219 accessions for all the quantitative characters studied except for the seed size. Among the traits, number of clusters per pod exhibited highest estimate of phenotypic coefficient of variance (PCV) (37.04) and genotypic coefficient of variance (GCV) (36.94) followed by 100-seed weight (g) (PCV=31.96, GCV=31.46) and number of branches per plant (PCV=29.56, GCV=29.18). Heritability was highest (>70%) for all the characters studied. High heritability coupled with high genetic advance as per cent mean was recorded for plant height (cm), number of branches per plant, number of clusters per plant, number of pods per cluster, number of seeds per pod, pod length (cm), seed size (cm) and 100-seed weight (g). Hundred seed weight (g) exhibited highly significant and positive correlation with seed size (cm) (0.68) and pod length (cm) (0.17). A very wide range of variability was observed for 11 qualitative traits in the working collection and this can be potentially used for the improvement of soybean for yield and related traits.